1979
DOI: 10.1111/j.1399-6576.1979.tb01480.x
|View full text |Cite
|
Sign up to set email alerts
|

Embryotoxicity and Fertility Study with Halothane Subanesthetic Concentration in Rats

Abstract: The effect of 9 ppm halothane, a subanesthetic concentration, was studied on the reproductive ability and pregnancy outcome in white rats. Pregnant females were exposed for 4 h per day during the whole gestation period. Male animals were subjected to halothane inhalation for 4 h daily, 5 days per week for 6 or 8 months. In the exposed females higher rates were established for early interruption of pregnancy (all implants dead) and for embryonic death in the later periods of intrauterine life compared to contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…reported fetal resorption in rats even at very low concentrations (9 ppm). 60 Several bio-monitoring studies have suggested the existence of a strong relationship between exposure to halogenated anesthetic gases and the risk of genotoxicity for surgery room staff. It has been observed that nitric oxide can interfere with vitamin B12 and irreversibly deactivate methionine synthase in CNS.…”
Section: Anesthetic Gasesmentioning
confidence: 99%
“…reported fetal resorption in rats even at very low concentrations (9 ppm). 60 Several bio-monitoring studies have suggested the existence of a strong relationship between exposure to halogenated anesthetic gases and the risk of genotoxicity for surgery room staff. It has been observed that nitric oxide can interfere with vitamin B12 and irreversibly deactivate methionine synthase in CNS.…”
Section: Anesthetic Gasesmentioning
confidence: 99%
“…[ 7 8 9 ] Animal studies reported teratogenicity and fetal death following exposure, with even fetal death reported after 9 ppm exposure in a case. [ 10 11 ] Blokker-Veldhuis et al . have recently expressed concern about the potential effects of occupational exposure although the data on adverse health responses still remain inconclusive.…”
mentioning
confidence: 99%